# IS IT POSSIBLE TO SOLVE FOR m2 from a(m1+m2) = (m2g-m1g)?

1. Nov 24, 2009

### tigerwoods99

1. The problem statement, all variables and given/known data

a=(m2g-m1g)
------------- divided by IS IT POSSIBLE TO SOLVE FOR m2 =????
(m1+m2) where g = gravity

2. Relevant equations

a(m1+m2) = (m2g-m1g)
where g = gravity

3. The attempt at a solution

a(m1+m2) = (m2g-m1g)

IS IT POSSIBLE TO SOLVE FOR m2 =???? where g = gravity

THANKS!!!!

2. Nov 24, 2009

### Staff: Mentor

You can certainly isolate it on one side of the equation to get m2 = ___________

Whether you can "solve" for it depends on if you have "a" and "m1" as knowns.

3. Nov 24, 2009

### Unto

lol..

<< most of solution deleted by berkeman >>

This however looks completely ridiculous, what is it you are trying to solve??

4. Nov 24, 2009

### Staff: Mentor

Please remember not to do the OP's homework for them. We can offer tutorial help, but do not work their equations for them. Thanks.

5. Nov 24, 2009

### tigerwoods99

Thanks! i just solved it myself lol. i got m2 = (-m1a-m1g)/(a-g) but i guess i will multyply by -1/-1 to make it (m1a+m1g)/g-a

and im trying to solve an atwood machine problem. For example, 1 mass is given and the other is not given, and you know the acceleration so m2 = blabla really helps!!